IMPLEMENTASI KEBIJAKAN PENEMPATAN APARATUR SIPIL NEGARA PADA JABATAN STRUKTURAL TAHUN 2016-2019 BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KABUPATEN MIMIKA - Elanus Deikma (Universitas Cenderawasih, 2020)
This research was conducted at the Mimika Regency Regional Civil Service Agency. The researched problems aim to find out any indication of apparatus placement that is not in accordance with the regulations. Therefore this research requires primary and secondary data. The data is obtained through direct observation or observation, questionnaires and interviews. Once collected, it is then analyzed using qualitative descriptive techniques, namely an analysis that seeks to provide a detailed picture based on the reality in the field and the results will be presented in tabular form and equipped with descriptions and supporting information to draw conclusions and give some suggestions. The formulation of the problem of writing this thesis is how the placement of the Apparatus in the Regional Personnel Agency of Mimika Regency. The purpose of this research is to determine the implementation of the placement of the Apparatus in the Mimika Regency Regional Civil Service Agency. In this study, the implementation of apparatus placement at the District Civil Service Agency, Mimika is measured by 5 indicators, namely, existing academic education / achievement, secondly experience, third is physical and mental health, fourth is marital status, and the fifth is apparatus age. Based on the results of the author's research, it can be concluded that the implementation of the placement of employees at the Regional Personnel Agency of Mimika Regency has been carried out well. Because in accordance with the factors considered in the placement of Regional Civil Servants.